PREPARATION OF FINANCIAL STATEMENTS BASED ON SAK EMKM USING SPREADSHEET ON MSMEs IN BUKITTINGGI - Rita Rahayu; Verni Juita; Denny Yohana; Rahmi Desriani; Sri Dewi Edmawati; Abdul Karib (Warta Pengabdian Andalas, 2021)
This activity aims to increase Small Medium Micro Enterprises (MSME) managers' capacity in preparing financial reports by the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) using a spreadsheet application. Implementing this activity was by providing training to MSMEs in Bukittinggi on financial management using a Microsoft Excel-based application previously developed by the team. MSMEs can use eight main menus to manage their finances in this simple application. The menus are Account List, Code List, Journal, Ledger, Work Sheet, Subsidiary Ledger, Income Statement and Statement of Financial Position. The MSME owners will fill in these menus according to their activities and transactions. 17 MSMEs in Bukittinggi participated in this activity. The results of this activity show that the application makes it easier for MSME managers to understand financial management, and it also assists them in preparing their financial statements. This activity contributed to MSMEs improving their capabilities related to transaction recording and financial reporting based on Financial Accounting Standards.